Pemikiran Al-Ushaili Terkait Tahapan Pemerolehan Bahasa Kedua - Taufiqurrohman Taufiqurrohman (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2023)
The study of second (foreign) language acquisition or called second language acquisition (SLA)/foreign language acquisition (FLA) can be understood as an intradisciplinary field of science that seeks to uncover factors outside language in the process of acquiring a second (foreign) language such as psychosocial factors. and social factors. These factors are the disciplines of psycholinguistics, sociolinguistics, or neurolinguistics that influence the process of acquiring a second (foreign) language. Al-Ushailli is a modern Arabic language figure who has a great concern in the field of psycholinguistics as well as teaching Arabic. Al-Ushailli divides the second stage of language acquisition into five stages: Silent/pre-production period, early production, speech emergence, intermediate fluency, continued language development.